How is the Advocacy Coalition Framework Doing? Some Issues since the 2014 Agenda. - Ma, Janaína; Cirilo Lemos, Marco Aurélio; Mota Vieira, Diego (Revista Brasileira de Ciência Política, 2020)
This article presents an international review of the Advocacy Coalition Framework (ACF) from 2015 to 2018. Forty-six empirical works that use the ACF as the main model or one of the main models for the analysis of public policies were analyzed. Bibliometric data, research methodologies and theoretical components have been considered in this analysis. In addition, this article fills in a gap in previous reviews of the ACF by presenting an exploratory review of ACF applications in Latin America. Our conclusions show that the research agenda proposed in 2014 has evolved over the last few years, but still presents unexplored challenges and possibilities for researchers interested in the use of ACF. We also offer some recommendations for future research.